The effects of endometrioma size and bilaterality on ovarian reserve - (:unkn) unknown (TAYLOR & FRANCIS INC, 2020)
The aim of this study was to investigate the effects of endometrioma (OMAs) size and bilaterality on ovarian reserve. The patients with OMA were determined by ultrasonographic examination. Fifty patients with unilateral OMA (Group A), 30 patients with bilateral OMA (Group B), and 60 women without ovarian cysts (Group C) were included in this study. AMH levels were measured, and antral follicle count (AFC) was determined. The mean serum AMH levels were significantly lower in Group B than Groups C and A, and were significantly lower in Group A than Group C. There was a significant correlation between serum AMH level and OMA size in Group A (R = -.372, p = .008). OMAs per se appear to be associated with damage to the ovarian reserve. Increased OMA size is related to decreased AMH levels in patients with OMA. Bilateral OMAs have a more destructive effect on ovarian reserve.IMPACT STATEMENT What is already known on this subject? Previous Studies have demonstrated the effect of surgery on ovarian reserve but there have been contradictory findings reported about the effects of OMAs per se on serum AMH levels and it has not been clear what the relation between OMAs size and AMH levels is, if any. What the results of this study add? In this study, we found decreased AMH levels in patients with OMA. The results showed significant negative correlation between OMA size and AMH levels. The patients with bilateral OMAs had lower AMH levels than the unilateral ones.
Keywords: AMH; endometrioma; ovarian reserve; endometrioma size; endometriosis; NEGATIVELY AFFECT; HORMONE-LEVELS; WOMEN; DIAGNOSIS; ULTRASOUND; ACCURACY; DECLINE; BENIGN; IMPACT; CYSTS